2015
DOI: 10.1186/s12888-015-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with Posttraumatic Stress Disorder seven years after the conflict in three districts in northern Uganda (The Wayo-Nero Study)

Abstract: BackgroundResearch on the prevalence of Posttraumatic Stress Disorder (PTSD) is still limited in low income countries yet PTSD can be a public health problem in post conflict areas. In order to respond to the burden of PSTD in northern Uganda, an area that experienced civil strife for over two decades, we need accurate data on its (PTSD) prevalence and the associated risk factors to facilitate public mental health planning.MethodsThis study employed a cross-sectional study design and data collection was undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 37 publications
5
64
9
Order By: Relevance
“…More in detail, suicide ideation was reported in 12.4 % and a suicide attempt in 17,1% of patients attending a specialized HIV/AIDS clinic before the antiretroviral treatment (ART) era in Uganda; while the suicidal ideation rate was 13 % in the same setting in post-ART Uganda (Kinyanda et al, 2015). The reason for these higher rates could be explained by differences in location.…”
Section: General Findingsmentioning
confidence: 87%
See 3 more Smart Citations
“…More in detail, suicide ideation was reported in 12.4 % and a suicide attempt in 17,1% of patients attending a specialized HIV/AIDS clinic before the antiretroviral treatment (ART) era in Uganda; while the suicidal ideation rate was 13 % in the same setting in post-ART Uganda (Kinyanda et al, 2015). The reason for these higher rates could be explained by differences in location.…”
Section: General Findingsmentioning
confidence: 87%
“…Previous studies have indicated comorbidity between suicidality and psychiatric disorders, in particular with depression and PTSD (Wasserman et al, 1999;Ovuga et al, 2005;Kiyanda et al, 2015;Casey et al, 2006;Nock et al, 2008), though few studies have used formal diagnostic criteria (Wasserman et al, 1999) as in the current study. The high prevalence of major depressive disorder (at a rate of 24.7 %; Mugisha et al 2015) and PTSD (at a rate of 11.8 %, Mugisha et al, 2015) could explain the high rates of suicide attempt and ideation.…”
Section: General Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The health and nutrition status of refugees represents a major public health concern, and to the best of our knowledge, this is the first study to examine the relationship between food security and common mental disorders in a refugee population in South Africa; although previous studies have found evidence for such a relationship within conflict-affected and internally displaced populations in other low- and middle-income countries (LMICs), such as Uganda [21] and Sri Lanka [22]. The results indicate a high prevalence of food insecurity in this population in South Africa; and that food insecurity has an impact on their mental health status, particularly contributing to an increase in depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%